MENYELESAIKAN MASALAH DI ANTARA SESAMA ANGGOTA JEMAAT BERDASARKAN PETUNUJUK YESUS DI MATIUS 18:16 DENGAN MEMANGGIL SAKSI-SAKSI - Gerry Takaria (Fakultas Filsafat Universitas Advent Indonesia, 2016)
Jesus gave the right steps in resolving conflicts among the people of God. Thesecond phase after meeting privately is to call witnesses who can help resolve theproblem. There are two types of witnesses who need to be considered to help solvethose problems, the first witnesses are those regarded as wise, trustworthy, impartialand have the motivation to help in resolving the problem, and the second witness isone who sees or record an event that never happened and honestly, impartially anddared to tell the truth.